2021
DOI: 10.1155/2021/2929233
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Differential Value of Tumor Marker CA724 on Primary Gastric Cancer

Abstract: We investigated the diagnostic value of the tumor marker CA724 in patients with primary gastric cancer. One hundred forty-six patients with primary gastric cancer were selected as the observation group; 89 patients with gastritis treated in the same period were included in the control group 1; 91 patients with healthy physical examination during the same period were included in the control group 2. Electrochemiluminescence immunoassay was used to determine the level of carbohydrate antigen CA724 in each group;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…CA724 is a high molecular weight glycoprotein. Studies have shown that CA724 is increased in the serum levels of patients with GC, CRC and breast cancer (BC) [ 21 – 24 ], and it has good diagnostic performance for gastrointestinal tumors [ 25 ]. However, other studies have found that CA724 is not only expressed in tumor tissues but also highly expressed in the serum of gout patients [ 26 ] and moderately expressed in normal tissues of secretory endometrium and transitional colon mucosa [ 27 ]; this indicates that CA724 is not the exclusive product of tumor cells, rendering the role of CA724 as a predictor of gastrointestinal tumors controversial.…”
Section: Discussionmentioning
confidence: 99%
“…CA724 is a high molecular weight glycoprotein. Studies have shown that CA724 is increased in the serum levels of patients with GC, CRC and breast cancer (BC) [ 21 – 24 ], and it has good diagnostic performance for gastrointestinal tumors [ 25 ]. However, other studies have found that CA724 is not only expressed in tumor tissues but also highly expressed in the serum of gout patients [ 26 ] and moderately expressed in normal tissues of secretory endometrium and transitional colon mucosa [ 27 ]; this indicates that CA724 is not the exclusive product of tumor cells, rendering the role of CA724 as a predictor of gastrointestinal tumors controversial.…”
Section: Discussionmentioning
confidence: 99%
“…CA724 is one of the novel tumor markers, which was first discovered in 1981 and is widely used in the diagnosis of breast cancer and gastrointestinal tumor diseases. CA724 has a high sensitivity in the diagnosis of GC and can be detected in all stages, and is slightly superior to other tumor markers in the diagnostic efficacy of GC[ 37 , 38 ]. The results of this study were also consistent with that.…”
Section: Discussionmentioning
confidence: 99%